2015
DOI: 10.1084/jem.20150407
|View full text |Cite
|
Sign up to set email alerts
|

CHMP5 controls bone turnover rates by dampening NF-κB activity in osteoclasts

Abstract: Greenblatt et al. show that deletion of CHMP5 in osteoclasts leads to increased bone resorption coupled with exuberant osteoblast activity, resembling an early onset form of human Paget’s Disease of Bone

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 58 publications
4
51
0
Order By: Relevance
“…Raptor deletion in osteoclasts impaired bone resorption, which is important for bone modeling during bone development (3,24), which may disturb the normal developmental process and, ultimately, induce decreased body weight. This phenomenon was found in other mouse models too (25,26).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Raptor deletion in osteoclasts impaired bone resorption, which is important for bone modeling during bone development (3,24), which may disturb the normal developmental process and, ultimately, induce decreased body weight. This phenomenon was found in other mouse models too (25,26).…”
Section: Discussionsupporting
confidence: 67%
“…Cell Culture and Osteoclast Differentiation-For osteoclast differentiation analysis, 4-week-old mice were used to obtain BMMs from whole bone marrow following a method described previously (26,35). Briefly, bone marrow was washed out from the femora and tibiae and centrifuged at 500 ϫ g for 10 min.…”
Section: Mtorc1 Regulates Osteoclast Differentiationmentioning
confidence: 99%
“…Importantly, these results indicated that the overall conformation of the NOD2 protein is not compromised when fused to GAL4DBD and thus allows isolation of valid partners in Y2H. Several putative NIPs (PPP1R12C, LDOC1, ANKHD1, CHMP5 or IKBIP) were previously reported to be linked with the NF-κB signaling pathway, confirming their interest as potential candidates [30, 3841]. Others were involved in cellular trafficking, protein sorting or cytoskeletal architecture (CHMP5, DOCK7, VIM, SDCCAG3, KRT15, DCTN1, and GOLGB1) [4247] or as regulators of cell signaling (PPP2R3B, TRIM41) [48, 49].…”
Section: Resultssupporting
confidence: 57%
“…A very recent study of mice with an osteoclast-driven deletion of the NF-κB inhibitor CHMP5 has suggested the phenotype of exuberant BPagetic^periosteal remodelling in these mice results from an interaction of ephrinB2 in osteoclasts with EphB4 in osteoblasts [63]. In this work, high ephrinB2 mRNA levels were noted in cultured osteoclasts from these mice, likely a simple reflection of greater osteoclast numbers (also indicated by high mRNA levels of osteoclast markers).…”
Section: Ephrinb2 As a Mediator Of Pth And Igf-i Anabolic Actionssupporting
confidence: 57%